Carer administration of as-needed subcutaneous medication for breakthrough symptoms in people dying at home: the CARiAD feasibility RCT - Zoë Hoare; Clare Wilkinson; Dyfrig A Hughes; Anthony Byrne; Annmarie Nelson; Julia Hiscock; Bee Wee; Marlise Poolman; Annie Hendry; Stella Wright; Paul Perkins; Anne Parkinson; et al. (BMJ Open)
Objectives To determine if carer administration of as-needed subcutaneous medication for common breakthrough symptoms in people dying at home is feasible and acceptable in the UK, and if it would be feasible to test this intervention in a future definitive randomised controlled trial.Design We conducted a two-arm, parallel-group, individually randomised, open pilot trial of the intervention versus usual care, with a 1:1 allocation ratio, using convergent mixed methods.Setting Home-based care without 24/7 paid care provision, in three UK sites.Participants Participants were dyads of adult patients and carers: patients in the last weeks of their life who wished to die at home and lay carers who were willing to be trained to give subcutaneous medication. Strict risk assessment criteria needed to be met before the approach, including a known history of substance abuse or carer ability to be trained to competency.Intervention Intervention-group carers received training by local nurses using a manualised training package.Primary outcome measures Quantitative data were collected at baseline and 6–8 weeks post-bereavement and via carer diaries. Interviews with carers and healthcare professionals explored attitudes to, experiences of and preferences for giving subcutaneous medication and experience of trial processes. The main outcomes of interest were feasibility, acceptability, recruitment rates, attrition and selection of the most appropriate outcome measures.Secondary outcome measures The secondary outcome measure was time to symptom relief, calculated using data items from the carer diary, after the patient had died.Results In total, 40 out of 101 eligible dyads were recruited (39.6%), which met the feasibility criterion of recruiting >30% of eligible dyads. The expected recruitment target (≈50 dyads) was not reached, as fewer than expected participants were identified. Although the overall retention rate was 55% (22/40), this was substantially unbalanced (30% (6/20) usual care and 80% (16/20) intervention). The feasibility criterion of >40% retention was, therefore, considered not met. A total of 12 carers (intervention, n=10; usual care, n=2) and 20 healthcare professionals were interviewed. The intervention was considered acceptable, feasible and safe in the small study population. The intervention group had a considerably shorter time to medication administration than the usual-care group (median time to administer medication in intervention=5 min, usual-care=105 min). Intervention group carers felt confident in administering medication. Healthcare professional support was sought by intervention group carers in 24 out of 147 (16.3%) medication administration entries. The context of the feasibility study was not ideal, as district nurses were overstretched, unfamiliar with research methods and possibly not in equipoise. A disparity in readiness to consider the intervention was demonstrated between carers, who were uniformly enthusiastic, and healthcare professionals who were not. Findings confirmed methodological and ethics issues pertaining to researching the last days of life care.Conclusion The success of a future definitive trial is uncertain because of equivocal results in the progression criteria, particularly poor recruitment overall and a low retention rate in the usual-care group. Future work regarding the intervention should include understanding the context of UK areas where this has been adopted, ascertaining wider public views and exploring healthcare professional views on burden and risk in the NHS context. There should be consideration of the need for national policy and the most appropriate quantitative outcome measures to use. This will help to ascertain if there are unanswered questions to be studied in a trial.Trial registration number ISRCTN11211024.